Operationalizing intimacy and identity aspects of personality functioning in relation to personality disorder in adolescents - Cervantes, Breana R.; Kerr, Sophie; Vanwoerden, Salome; Sharp, Carla (Frontiers in Psychiatry, 2023)
According to dimensional models of personality pathology, deficits in interpersonal (intimacy and empathy) and self (identity and self-direction) function (Criterion A) are core to all personality disorders. These aspects of personality functioning (Criterion A) have seldom been evaluated for how they might relate to one another in the context of personality pathology in adolescents. Moreover, the use of performance-based measures to evaluate aspects of Criterion A function remains an untapped resource. Therefore, the present study aimed to evaluate relations between two features of Criterion A, maladaptive intimacy and maladaptive (or diffused) identity, in adolescence. For intimacy, we leverage a performance-based approach to studying intimacy, operationalized in a developmentally relevant way (perceived parental closeness). For identity, we rely on a validated self-report measure of identity diffusion. We examined the relationship between these features with each other and their relations with borderline features. Additionally, we explored whether identity diffusion mediated the expected relationship between perceived parental closeness and borderline features. We hypothesized that greater distance in perceived parental closeness would be associated with higher levels of borderline features, as well as higher levels of identity diffusion, and that identity diffusion would account for the relationship between intimacy and personality pathology. The sample included 131 inpatient adolescents (Mage = 15.35, 70.2% female). Results indicated that intimacy, operationalized as perceived parental closeness, with both mothers and fathers was significantly associated with levels of identity diffusion and borderline features. In addition, greater feelings of closeness with parents were associated with lower severity of borderline features via healthier identity function. Implications of the results, limitations, and future directions are discussed.